A case of non-small cell lung cancer with long-term response after re-challenge with nivolumab - Keima Ito; Tetsuya Oguri; Norihisa Takeda; Kensuke Fukumitsu; Satoshi Fukuda; Yoshihiro Kanemitsu; Tomoko Tajiri; Hirotsugu Ohkubo; Masaya Takemura; Ken Maeno; Yutaka Ito; Akio Niimi (Respiratory Medicine Case Reports, 2020)
A 76-year-old man was admitted to our hospital with cough and dyspnea. He was diagnosed with advanced lung cancer. Nivolumab was given as second-line treatment, cytotoxic chemotherapy was given as third-line treatment, and nivolumab re-challenge was given as fourth-line treatment. Thereafter, 41 chemotherapy courses were administered over 2 years. Currently, he is being followed with no recurrence at least 10 months after treatment. Thus, the case of a patient with advanced lung cancer who was previously unsuccessfully treated with nivolumab and then demonstrated a long-term clinical response to a re-challenge with nivolumab after cytotoxic chemotherapy and radiation therapy is presented. Keywords: Lung cancer, Nivolumab, Immune checkpoint inhibitors, PD-L1